Exercise in Polluted Spaces: Inflammatory Differentiation and Lung Mitochondrial Biogenesis - Lucky Angkawidjaja Roring; Amung Ma'mun; Hamidie Ronald Daniel Ray; Beta Paramita (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2023)
Indonesia is ranked as the most highly polluted country in Southeast Asia and the 26th on the list of the most polluted countries worldwide. Exercising in polluted spaces can have complex effects on inflammation and mitochondrial biogenesis in the lungs. The interaction between physical activity and pollution exposure may affect lung health. This study aimed to analyse the different effects of exercise in polluted open spaces and antioxidant administration on lung inflammation and mitochondrial biogenesis. The research approach used was a quantitative approach with a comparative descriptive design using random assignment technique. The research sample used male white rats (Rattus Norvegicus) Wistar strain aged 8-10 weeks with a body weight of 200-300 g obtained from Biofarma Animal Breeding Facility. The sampling technique used in this study was random assignment technique. In this study, the number of members of the treatment group was 5, so the total research sample amounted to 5 x 9, namely 45 samples. The results showed that there was a differentiation in the level of inflammation represented by the level of IL-6 and NF-κB and lung mitochondrial biogenesis level represented by PGC-1α, TOM20, and COX IV with moringa administration in physical activities, as indicated by the comparison of the mean values of the inflammatory process and lung mitochondrial biogenesis in the nine treatment groups. The implication of this research is that it is necessary to consider appropriate sport strategies or guidelines for individuals who exercise in a polluted environment to reduce the negative impact on the respiratory system and overall lung health.